2009
DOI: 10.1038/nature07979
|View full text |Cite
|
Sign up to set email alerts
|

Interior pathways of the North Atlantic meridional overturning circulation

Abstract: for the AMOC deep limb. In order to assess the impact of the interior pathway relative to the DWBC pathway, this work seeks to quantify the AMOC deep limb pathways in ocean circulation models, compare the pathway signatures of these models to observations, and identify a mechanism driving the interior pathway. The partitioning of the AMOC deep limb into interior and DWBC pathways is observed in several ocean models. Furthermore, there is a good agreement between the structure of the export pathways in models a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
249
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 253 publications
(296 citation statements)
references
References 48 publications
34
249
0
1
Order By: Relevance
“…LSW classes can even reach the European ocean margin van Aken, 2000;Yashayaev et al, 2007aYashayaev et al, , 2007b. This supports the ideas, expressed by Bower et al (2009), that interior pathways of the cold branch of the AMOC may be at least as important as the deep western boundary current.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…LSW classes can even reach the European ocean margin van Aken, 2000;Yashayaev et al, 2007aYashayaev et al, , 2007b. This supports the ideas, expressed by Bower et al (2009), that interior pathways of the cold branch of the AMOC may be at least as important as the deep western boundary current.…”
Section: Discussionsupporting
confidence: 73%
“…Entering the deep western boundary current along the American continental slope via such indirect pathways (Bower et al, 2009) LSW contributes to the south flowing North Atlantic Deep Water in the cold branch of the Atlantic meridional overturning circulation (AMOC). Because of the relatively high near-surface salinities outside the Labrador Sea, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…From Cape Farewell, the DWBC then travels around the Labrador Sea as the deep part of the West Greenland Current, passing through the 53°N array (Fischer et al, 2010 off southern Labrador in the Deep Labrador Current (DLC) and entering the open subpolar North Atlantic at Flemish Cap (Rhein et al, 2011) and finally (for this investigation) exits the subpolar regime at the tail of the Grand Banks . Besides the DWBC there also are interior routes along which North Atlantic Deep Water (NADW) either recirculates in the subpolar basin or is exported into the subtropics (Bower et al, 2009). However, in a comparative analysis of the currents and transports in a high resolution (0.08° grid) isopycnic HYCOM model, Xu et al (2013) show that the boundary flow at 53°N is correlated with the Meridional Overturning Circulation (MOC) transport across WOCE Line AR19 off the Grand Banks, and in an earlier study by Böning et al (2006) it has been shown that the deep water export from the Labrador Sea is correlated with the mid-latitude Meridional Overturning Circulation (MOC).…”
Section: ) Introduction and Objectivesmentioning
confidence: 99%
“…The data presented in Bower et al (2009) suggest that the horizontally curving slopes around the GB and Flemish Cap (FC) are associated with increased eddy generation relative to less curved portions. The curvature, convex or concave, we refer to is of isobaths, horizontal lines of constant bottom depth.…”
Section: Introductionmentioning
confidence: 99%
“…The task of measuring and characterizing eddy generation mechanisms is more challenging for deep (sub-surface intensified) boundary currents, since they are much less amenable to remote sensing, and since even after decades of oceanographic expeditions, in situ measurements are quite sparse. A prominent example is the variability associated with the Deep Western Boundary Current (DWBC) in the Grand Banks (GB) area, where eddy shedding and interior flow pathways are prevalent, as observational campaigns using deep Lagrangian floats have revealed (Lavender et al 2000(Lavender et al , 2005Bower et al 2009). …”
Section: Introductionmentioning
confidence: 99%